IMPLEMENTASI SISTEM INFORMASI DATA NILAI SISWA BERBASIS WEB PADA SMK NEGERI 1 NGULING - Endang Widia Astuti (SPIRIT, 2019)
State Vocational School 1 Nguling is one of the organizations in which there are teaching  and learning  activities  which  are  under  the  responsibility  of  a  school  principal.  All  activities that take place in a school cannot be monitored in its entirety without proper organization. For this reason, the implementation of  a web-based student value data information system is an alternative method of overcoming existing problems. By utilizing  the sophistication  of  existing  information  technology,  efficiency  in  the  process  of  inputting student  grades   will   be  increasingly met. One of the information technologies that can be applied is internet technology, by  utilizing  internet   technology, the process  of  inputing  student  grades  can  be  done  online.  in  addition,  with  this application  system,  students  can  easily  access  information  about  the  value  of  their  learning  outcomes  by using the  facilities  already  provided. That way the  nuances  of  IT  will  be  reflected  even  though  the  institution  is located ina rural area   Keywords: Value data information system